2009
DOI: 10.3144/expresspolymlett.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pyrolytic carbon black prepared from junked tires on the properties of ethylene-propylene-diene copolymers (EPDM)

Abstract: Abstract. Pyrolytic carbon black (PCB) made from used tires was used in ethylene-propylene-diene copolymers (EPDM). The microstructure of PCB was characterized by scanning electron microscopy (SEM). PCB was compounded with EPDM to prepare EPDM vulcanizates. The effects of PCB on the processing properties of EPDM compounds and the mechanical properties of vulcanizates were investigated and compared with other traditional fillers such as semi-reinforcing furnace black (N774), light calcium carbonate (CaCO3) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[14] Du et al found that PCB was similar to N774 for the reinforcement of styrenebutadiene rubber (SBR) [15] and to N990 for the reinforcement of ethylene-propylenediene rubber (EPDM). [16] Berki et al used PCB to partially replaced N330 in SBR, and found that the tear strength increased and fatigue performance was improved, but the tensile strength decreased. [17] Lai et al found that 20% N660 could be replaced by PCB without affecting the tensile strength of SBR.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Du et al found that PCB was similar to N774 for the reinforcement of styrenebutadiene rubber (SBR) [15] and to N990 for the reinforcement of ethylene-propylenediene rubber (EPDM). [16] Berki et al used PCB to partially replaced N330 in SBR, and found that the tear strength increased and fatigue performance was improved, but the tensile strength decreased. [17] Lai et al found that 20% N660 could be replaced by PCB without affecting the tensile strength of SBR.…”
Section: Introductionmentioning
confidence: 99%
“…There were some works investigating the potential possibilities of replacing commercial carbon black with PCB in terms of mechanical properties in the rubber compounds, such as natural rubber (NR)/styrene–butadiene rubber (SBR) blends, 12,13 SBR, 14 -16 ethylene–propylene–diene copolymers, 17 and NR. 18 Their results generally suggested that some of the mechanical properties were comparable with semi-reinforcing furnace blacks like N772 and N774 series in a certain percentage of replacement but inferior to high abrasive furnace black like N330 and N339 series, mainly due to the high ash content and low surface activity.…”
Section: Introductionmentioning
confidence: 99%
“…According to ASTM (American Society for Testing and Materials) standard classification, such results suggest a reinforcing potential close to N300 rubber-grade carbon blacks. Several studies using rCBs as partial or total virgin carbon black substitutes have been carried out to evaluate and investigate their reinforcing potential in rubber compounds such as NR/SBR blends [20,21], SBR [19,22,23] or EPDM [24]. The results obtained for the mechanical behavior of these vulcanized rubbers have been inferior to what was expected by physical and chemical characterizations following ASTM analytical standards.…”
Section: Introductionmentioning
confidence: 99%